Study on Water Resistant of Organic and Inorganic Fibre Panel Board - Khairuddin, Khairul Hafizie; Amiruddin, Muhammad Danish Hifzhan; Zamri, Muhammad Izzat; Ngadiman, Norhayati (Multidisciplinary Applied Research and Innovation, 2022)
Currently, with the environmental cautious, many studies show that the wooden panel board can be replaced with more environmental friendly materials such agriculture fibre and durable materials such as the fiberglass, coconut fibre, sugarcane bagasse and banana fibre. However, the different types of the panel board raw materials will occasionally contribute to the panel boards’ water resistant which is vital because water resistant can affect the strength of the panel board. Therefore, this study aim to compare the water resistant of the varies fibre panel boards. In addition, this study investigated method to enhance the water resistance property of fibre panelboard by reviewing previous studies. The methodology of this studies is by testing water absorption and swelling test of different types fibre panel board which are fiberglass panel board, coconut fibre panel board, sugarcane bagasse panel board, banana fibre panel board. By reviewing through the 19 articles and journals using three stages process which is identification screening, eligibility and included to identify the method to increase water resistance of fibre panel board. Based on the results, the fiberglass has the highest density which is and 0% of water absorption and swelling test. Meanwhile, the sugarcane bagasse has the lowest density which is and highest in water absorption and swelling test which is 108% and 3%. Thus, the finding indicate that higher values of density will provide better water resistance in panel board. In a nutshell, the fiberglass panel board is much better than the conventional wood panel board in terms of water resistant however, the fiberglass will be slight costly. In order to reduce the cost, the fibre panel boards can be layered with polyurethane coatings in order to enhance the water resistance properties of the fibre panelboard.